DIRECTIVE SPEECH ACTS IN ELLA ENCHANTED MOVIE - Nggus, Yohana Cellina (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
Speech acts refer to the action performed by produced utterances. Speech acts are found not only in everyday life but can also be found in a movie or novel, but this study discussed about speech acts in a movie. People can perform an action by saying something. The directive speech act is used when the speaker wants the hearer to do something for him or her. The directive speech acts consist of activities such as requesting, commanding, questioning, order and suggesting. This research aimed at finding the function of directive speech act in Ella Enchanted movie. The method used in this research was the descriptive qualitative method to describe the data in words and sentences containing directive speech acts. The data were collected from Ella Enchanted movie. The steps of data collection were watching and reading the movie script, then identifying, classifying and describing the data qualitatively. The data was taken from the movie script. The theory proposed by Searle (1969) and Austin (1962) was used to identify the types of directive speech act that was relevance in this movie. The data were classified into four directive speech act functions; they were 33 data categorized in Commanding, 6 data categorized in Asking, 16 data categorized in Requesting, and 12 data categorized in Ordering.